Kehidupan dan Pengaruh Simon Petrus dalam Teologi Kristen - Yakub Fransisko; Devi Lestary; Sarmauli Sarmauli (Berkat : Jurnal Pendidikan Agama dan Katolik, 2024)
This study aims to examine the life and influence of Simon Petrus, one of the closest disciples of Jesus Christ, in the context of Christian theology. From an ordinary fisherman, Petrus underwent a significant transformation into an early Church leader, marked by the change of his name to "Petrus," meaning "rock." This study explores Petrus important role in the spread of the gospel and the development of Christian doctrine, as well as the impact of his teachings on the understanding of Christian faith today. The method used is a qualitative approach with an analysis of literature, including biblical texts and relevant theological sources. The findings show that Petrus experience of denying Jesus and his restoration after Jesus' resurrection reflect human vulnerability and the power of forgiveness. Petrus teaching on salvation through faith is the basis for many Christian doctrines, including the concepts of redemption and eternal life. This study concludes that a deeper understanding of Petrus authority and role in various Christian traditions can provide valuable insights for modern church practice, as well as emphasize the importance of forgiveness and perseverance in faith for Christians today.